The interaction of local people and natural area in Haraz drainage basin; Case study: Ab-e Ask village - Rakhshan, Mojdeh; Mahmoudi, Hossein; Abdoli, Asghar; Veisi, Hadi; Babrgir, Sima (Frontiers in Water, 2023)
According to the importance of Locals impact on conservation, this research had tried to find the role of locals in the protection of natural resources and ecosystems, and also tried to clarify the external laws which are affecting on local’s livelihood. This research had done in Ab-e-Ask village which is located on the edge of the Lar National Park and along the Haraz River, which is one of the five protected rivers in Iran, and it used the public participatory methods. Using the “Problem Tree”, “Before and After Diagram”, “Social Resources Map” and etc. helped us to find the answers of: 1. The main reasons of water pollution 2. The land ownership`s effect on livelihood 3. Finding the traditional approaches of conservation. Finally, the results were about: 1. The sewage of Haraz Road Restaurants and also the pollution of fish ponds were the main water pollution reasons. 2. The effect of Land Ownership Law was clarified and 3. There were two Local Traditions that protect the natural resources, one was called “Barf-e-Chal” which was about saving the water sources for the summer, and the other was about protecting the plants of region until the end of pollination season that results in protecting the flora.